Dynamic cracking behavior of rocks - Gan, Boon Siong (2013)
The main purpose of this study was to investigate the cracks initiation and propagation processes of the moulded gypsum specimens with a single pre-existing flaw. Rock-like artificial gypsum specimens were moulded by mixing hydrocal gypsum cement with celite powder and water. The flaw with seven different flaw inclinations was pre-defined on the gypsum specimen. The gypsum specimen will be loaded with different strain rate under quasi static loading and dynamic loading test. Dynamic loading test will be performed by the apparatus called split Hopkinson pressure bar. A unixial compression machine will be used to complete the quasi loading test. The process of cracks initiation and propagation of the gypsum specimens are hardly to be observed by naked eyes. Therefore, a high speed camera system with the capability to capture 40,000 frames per second was used to record the entire fracturing process. A pair of strain gauges was attached at the middle of incident and transmitter bars. At the same time, the strain meter with highly sensitivity was used to collect the strain-time histories. The result shows that the average compressive strength obtains from quasi loading tests with single pre-existing flaw are much lower than the results obtained from dynamic loading test. The minimum compressive strength obtained from quasi static test and dynamic loading test are 23.3 MPa and 94 MPa respectively. The compressive strength for dynamic loading test is approximately four times higher than quasi static test. In the study of fracturing cracks, the images observed from the high speed camera shows that the tensile wing cracks was the first cracks occurred in the uniaxial compression and SHPB test. Conversely the secondary crack patterns obtained from SHPB test are different with the uniaxial test. This study proved that the fracturing patterns are highly affected by the strength of material and loading.